Merit of APACHE II, MPI and ARPI scores as determinants On Demand Relaparotomy - Kamil, Radhita F.; Lalisang, Toar JM; Kekalih, Aria (The New Ropanasuri Journal of Surgery, 2016)
Introduction. Delayed in decision making to carry out relaparotomy increases the morbidity and mortality. The decision to be made on demand relaparotomy is a kind of one subjectivity on the clinical setting. Therefore, it is necessary to have a thorough physical examination with additional diagnostic tools as the rationale to make an accurate decision that is the scoring system. There were many scoring systems has been proposed, and we run a study aimed to find out the merit of those scoring. Method. We run a case-control study enrolled 32 subjects with on demand relaparotomy and 64 subjects with laparotomy for any indication. APACHE II, MPI, ARPI scores were applied as variables. Data collected retrospectively from those who underwent laparotomy andrelaparotomy in RS dr.Cipto Mangunkusumo General Hospital in period of January 2012 to December 2013. These variables subjected to statistical analysis. Results. Based on statistical analysis of the two groups we found that APACHE II showed no significant difference (p = 0.114), whilst MPI and ARPI showed significant difference (p <0.0001). ROC curve showed that APACHE II had AUC of 59.2% with a cut-off point of 10, MPI had AUC of 86.4% with a cut-off point of 20 and ARPI had AUC of 77.6% with a cut-off point of 10. Conclusion. MPI and ARPI could be used as determinants on demand relaparotomy.